Rac1 in Muscle Is Dispensable for Improved Insulin Action After Exercise in Mice - Sylow, Lykke; Møller, Lisbeth L. V.; D'Hulst, Gommaar; Schjerling, Peter; Jensen, Thomas E.; Richter, Erik A. (Endocrinology (Philadelphia), 2016)
Exercise has a potent insulin-sensitivity enhancing effect on skeletal muscle, but the intracellular mechanisms that mediate this effect are not well understood. In muscle, Ras-related C3 botulinum toxin substrate 1 (Rac1) regulates both insulin- and contraction-stimulated glucose transport and is dysregulated in insulin resistant muscle. However, whether Rac1 is involved in mediating enhanced insulin sensitivity after an acute bout of exercise is unresolved. To address this question, we investigated after exercise whole-body (insulin tolerance test) as well as muscle (insulin-stimulated 2-deoxyglucose transport in isolated soleus muscle) insulin sensitivity in inducible muscle-specific Rac1 knockout (mKO) and wild-type (WT) littermate mice. Previous exercise enhanced whole-body insulin sensitivity by 40% in WT mice and rescued the insulin intolerance in Rac1 mKO mice by improving whole-body insulin sensitivity by 230%. In agreement, previous exercise significantly improved insulin sensitivity by 20% in WT and by 40% in Rac1 mKO soleus muscles. These findings suggest that muscle Rac1 is dispensable for the insulin sensitizing effect of exercise. Moreover, insulin resistance in Rac1 mKO mice can be completely normalized by previous exercise explaining why insulin resistant patients can increase insulin action with exercise despite dysfunctional Rac1 activity in muscle.